Beneficial Effects of Catalpol Supplementation during In Vitro Maturation of Porcine Cumulus-Oocyte Complexes - Yanxin Wang; Ye Xu; Sijia Li; Xi Yan; Xiaofen Yang; Mengjia Chen; Yun Wang; Ruru Jia; Dongping Zhou; Deshun Shi; Fenghua Lu (Antioxidants, 2023)
Oxidative stress degrades oocytes during in vitro maturation (IVM). Catalpol, a well-known iridoid glycoside, exhibits antioxidant, anti-inflammatory, and antihyperglycemic effects. In this study, catalpol supplementation was tested on porcine oocyte IVM and its mechanisms. Corticalgranule (GC) distribution, mitochondrial function, antioxidant capacity, DNA damage degree, and real-time quantitative polymerase chain reaction were used to confirm the effects of 10 μmol/L catalpol in the maturation medium during IVM. Catalpol treatment significantly increased the first-pole rate and cytoplasmic maturation in mature oocytes. It also increased oocyte glutathione (GSH), mitochondrial membrane potential and blastocyst cell number. However, DNA damage as well as reactive oxygen species (ROS) and malondialdehyde (MDA) levels. Mitochondrial membrane potential and blastocyst cell number were also increased. Thus, the supplementation of 10 μmol/L catalpol in the IVM medium improves porcine oocyte maturation and embryonic development.